Plasma free tissue factor pathway inhibitor (TFPI) levels and TF-induced thrombin generation ex vivo in men with low testosterone levels - Agledahl, Ingvild; Brodin, Ellen; Svartberg, Johan; Hansen, Bjarne (Thrombosis and Haemostasis, 2009)
Low testosterone levels in men have been associated with cardiovascular risk factors, some prothrombotic factors, and lately also an increased risk of both cardiovascular disease and all-cause mortality. Experimental studies have shown increased synthesis and release of tissue factor pathway inhibitor (TFPI) by physiological levels of testosterone in endothelial cells. Our hypothesis was that elderly men with low testosterone levels would have lower plasma levels of plasma free TFPI with subsequent increased thrombin generation. Elderly men with low (n=37) and normal (n=41) testosterone levels were recruited from a general population, and tissue factor (TF)-induced thrombin generation ex vivo and plasma free TFPI Ag were measured. Elderly men with low testosterone levels had lower plasma free TFPI Ag (10.9 ± 2.3 ng/ml vs. 12.3 ± 3.0 ng/ml, p=0.027) and shorter initiation phase of TF-induced coagulation assessed by lag-time (5.1 ± 1.0 min vs. 5.7 ± 1.3, p=0.039). The differences between groups remained significant and were strengthened after adjustment for waist circumference and other cardiovascular risk factors. Lag-time increased linearly across quartiles of plasma free TFPI Ag (p<0.001). Multiple regression analysis revealed that total and free testosterone were independent predictors of plasma free TFPI Ag. Our findings suggest that low testosterone levels in elderly men is associated with low plasma free TFPI Ag and subsequent shortened initiation phase of TF-induced coagulation.
Keywords: Men; testosterone; TFPI; thrombin generation